Valorization of cassava peel starch into functional liquid glucose via acid-catalyzed hydrolysis using sulfonated carbon catalyst and red ginger (Zingiber officinale var. rubrum) extract - Indah Retno Wulandary; Noor Laila; Yuniza Shentiya Dewi; Yulia Nurul Ma'rifah; Iryanti Fatyasari Nata; Ahmad Farhan Hadtimin (Konversi, 2025)
The growing gap between sugar consumption and domestic product in Indonesia Highlights the need for alternative sweeteners derived from renewable resources. This study investigates the synthesis of functional liquid glucose from cassava peel starch through hydrolysis catalyzed by sulfonated carbon derived from palm empty fruit bunches (TKS-SO3H) and the enhancement of its antioxidant properties by red ginger extract. The TKS-SO3H catalyst was prepared via carbonization at 350 C followed by sulfonation at 180 C, yielding an H+ ion concentration of 1.745 mmol/g. Hydrolysis was conducted at 100 C for 60 minutes with a catalyst loading of 5% (b/v) and starch concentration ranging from 2.5 to 7.5%. The optimum glucose concentration of 4.14 mg/mL was achieved at 5% starch concentration, demonstrating the effective catalytic performance of TKS-SO3H. subsequently, liquid glucose was combined with red ginger extract in various volume ratios (1:1-1:4 v/v) to assess antioxidant capacity using the DPPH radical scavenging assay. The formulation with a 1:4 glucose-to-ginger ratio exhibited the highest scavenging activity of 48.63% after 10 minutes, indicating a significant enhancement of functional properties. The findings suggest that cassava peel, an agricultural by-product, can be utilized as a sustainable feedstock to produce bifunctional liquid glucose using an environmentally benign heterogeneous catalyst, contributing to the development of value-added and health-oriented sweeteners.